SEXUAL DYSFUNCTION IN DIFFERENT DOMAINS AFFECTING HYPERTENSIVE PATIENTS- TIME TO ACT - Dr. Ankit Halder,; Dr. Navna Panchami,; Dr. Avinanda Biswas,; Dr. Dhakshana Pushpanathan,; Dr. Aditya Nair, (EPRA International Journal of Multidisciplinary Research (IJMR), 2022)
Sexual Dysfunction due to Hypertension and antihypertensives is well established in literature. Not only Erectile Dysfunction in males or lack of Sexual Desire in both genders are the only outward manifestations. Many other domains are equally affected that impair an individual from leading a sexually satisfying life. These become the core behind many psychiatric illnesses in them due to the its stress provoking capacity and impairments in other aspects of life too. Developing nations like India are mostly affected in this regard. Detailed longitudinal study and response to treatment in Indian scenario is the current need specially in Indian scenario.